Cultural Resilience in North American Indian First Nations - G. Brent Angell (University of Windsor, 2018)
Protective factors, needed for personal resilience, are known to vary from culture to culture. As such, social workers are faced with having to increase their knowledge and competence when working cross-culturally. In a bid to advance this understanding, this paper takes a culturally sensitive look at resilience in North American Indian First Nations. Founded on an interview with a colleague, this inquiry considers the interplay of self-concept, family, and culture in the development of protective factors in resilience. Implications for practice employing an understanding of cultural resilience are discussed. A combination of genetics and experience affects how we cope with matters ranging from mischance to catastrophe (Flach, 1997; Fraser, 1997; Kirby & Fraser, 1997; Wolin & Wolin, 1993). However, it is difficult to deconstruct this biopsychosocial entanglement into a triaged series of component steps. As such, the wrangling over the protective factor pecking-order remains somewhat moot (Butler, 1997). What is certain is that the focus of coping and change, from a social work perspective, lies in our ability to comprehend the psychosocial factors affecting resilience (Angell, Dennis & Dumain, 1997). We do know that individuals develop protective factors as a means of remedying or abating the effects of life-events that place them at risk (Rutter, 1987). Protective and risk factors are not merely opposite ends of a continuum, but rather are sequential links in the developmental chain of resiliency (Smith, Lizotte, Thronberry & Krohn, 1995). However, as Kirby and Fraser (1997) and Coie et al. (1993) note, what is considered to be a protective factor in one culture could invariably be determined a risk factor in another. This in and of itself is not problematic until such time as a member of a particular culture attempts or is forced to bridge his or her culture with that of another. What is certain is that the family, the main conduit of culture, is a keystone protective factor determinate of ...